Role of Health-Related Discrimination on Academic Performance Among Children with Congenital Heart Disease - Aliba Syed; Timothy Dixon; Dmitry Tumin; Meredith Sooy-Mossey (Pediatric Cardiology, 2026)
Abstract Congenital heart disease (CHD) can lead to neurodevelopmental impairments and increased need for routine healthcare visits, potentially leading to deficits in academic performance. Children with CHD may also experience health-related discrimination in school and clinical settings. To determine the association of health-related discrimination (independent of bullying) with academic performance and school absenteeism among children with CHD. We analyzed data on schoolchildren with CHD from the 2022–2023 National Survey of Children’s Health (NSCH). Our primary exposure was health-related discrimination towards the child, based on caregiver report, with bullying included as one of the covariates. Our outcomes were children’s academic performance categorized as excellent, good and poor and school absenteeism dichotomized into 0–10 and 11 or more missed school days. Based on a sample of 1,058 children, approximately 10% experienced caregiver-reported health-related discrimination. On bivariate analysis, caregiver-reported health-related discrimination was associated with lower academic performance and higher school absenteeism. On multivariable analysis, bullying was significantly associated with both lower academic performance (OR: 0.57; 95% CI: 0.36, 0.89; p = 0.013) and higher odds of school absenteeism (OR: 2.30; 95% CI: 1.11, 4.74; p = 0.025), but there were no significant associations between caregiver-reported health-related discrimination and children’s academic performance (OR: 0.76; 95% CI: 0.37, 1.56, p = 0.452) or school absenteeism (OR: 0.67; 95% CI: 0.26, 1.71, p = 0.404). As health-related discrimination is a broad term encompassing discrimination from peers, teachers and healthcare providers, bullying may be a more relevant determinant of school performance among children with CHD.